Comparing Complications, Functional And Oncological Outcomes Of Partial Versus Total Adrenalectomy: A Systematic Review And Meta-Analysis Of Literature - Kashi, Amir H; Simforoush, Nasser; Zargar, Homayoun; Sotoudeh, Mehdi; Nikbakht, Mohammad Javad; Golmohammadi, Melika (Urology Journal, 2026)
Purpose: Surgical management is a key component in treating adrenal masses, particularly when they are functional or large. However, the choice between partial adrenalectomy (PA) and total adrenalectomy (TA) remains controversial. Therefore, this systematic review and meta-analysis aimed to evaluate whether surgical outcomes differ between patients undergoing PA versus TA. Materials and methods: Following PRISMA 2020 guidelines, we systematically searched PubMed, Scopus, Web of Science, and the Cochrane Library for studies published up to April 2025. Nineteen studies were included, and methodological quality was assessed using the Newcastle–Ottawa Scale (NOS). A random-effects meta-analysis was conducted to estimate pooled outcomes. Results: A total of 19 studies comprising 3,165 patients were included, of whom 1,084 underwent partial adrenalectomy (PA) and 2,081 underwent total adrenalectomy (TA). PA was associated with a significantly higher risk of tumor recurrence compared with TA (RR = 2.64, 95% CI 1.55-4.51), while no significant differences were observed for metastasis or mortality. In contrast, PA significantly reduced the risk of postoperative steroid dependence (RR = 0.44, 95% CI 0.34-0.55) and adrenal insufficiency (RR = 0.49, 95% CI 0.34-0.70). Perioperative complications were less frequent following PA (RR = 0.56, 95% CI 0.40-0.78), particularly mild complications, with no differences in severe complications. There were no significant differences in operative time or intraoperative blood loss between the two techniques. Subgroup analyses demonstrated higher recurrence rates in pheochromocytoma among patients undergoing PA, compared with Conn’s adenoma. Perioperative complications were less frequent in PA in patients with Conn’s adenoma. No significant differences were observed regarding surgical laterality (left vs. right) or the operative approach (transperitoneal vs. retroperitoneal laparoscopic / robotic surgery). Conclusion: PA offers superior preservation of adrenal function and fewer mild perioperative complications compared with TA, but shows a higher risk of tumor recurrence in pheochromocytoma patients. PA was not associated with higher recurrence in Conn’s patients. Other surgical and oncological outcomes were similar, underscoring the need to individualize the choice of procedure based on tumor type and patient factors.